ANALYSIS OF AGRICULTURAL TECHNOLOGIES AND ADOPTION EFFICIENCY IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Sani. M. H.; Kushwaha, S.; Madaki, M. Y. (Journal of Agripreneurship and Sustainable Development, 2018)
The study analyzed the agricultural technologies and adoption efficiency in Western agricultural zone of Bauchi State, Nigeria. The study employed multi-strata fixed proportion random sampling from each village settlement making a total sample of 80 farmers of irrigated farm categories (small, medium and large farms) for the study. Similarly, 200 farmers that enrolled in the E-wallet agricultural technology were randomly selected for the study. Primary data were collected using well framed pre-tested questionnaire. The data were analyzed using, descriptive statistics, Adoption Index and probit regression analysis. The findings showed that 80% of owners of large farms and medium farms (65%) were high adopters and about 48% of the owners of small farms were medium adopters. The results of the probit regression revealed that household size, farming experience, attending agricultural exhibition and consulting newspaper were all significant (P<0.05), farm size (P<0.10) and extension contact (P<0.01) in farmers’ adoption of the E-wallet agricultural technology. The major constraints to E-wallet agricultural input distribution method in the study area were inadequate registration point (27.24%), network problem (23.16%) and registration of non-farmers (20.43%). The study concluded that adoption level of agricultural technologies in the study area was positively related with age, level of education and farm size. The study recommended that agricultural technologies of E-wallet inputs distribution in the study area should be sustained; virile extension services through private extension services, farmers to farmers’ extension approach should be encouraged in the study area.